Digestive duet: midgut digestive proteinases of Manduca sexta ingesting Nicotiana attenuata with manipulated trypsin proteinase inhibitor expression. - Jorge A Zavala (Public Library of Science (PLoS), 2008)
Background The defensive effect of endogenous trypsin proteinase inhibitors (NaTPIs) on the herbivore Manduca sexta was demonstrated by genetically altering NaTPI production in M. sexta's host plant, Nicotiana attenuata. To understand how this defense works, we studied the effects of NaTPI on M. sexta gut proteinase activity levels in different larval instars of caterpillars feeding freely on untransformed and transformed plants. Methodology/ principal findings Second and third instars larvae that fed on NaTPI-producing (WT) genotypes were lighter and had less gut proteinase activity compared to those that fed on genotypes with either little or no NaTPI activity. Unexpectedly, NaTPI activity in vitro assays not only inhibited the trypsin sensitive fraction of gut proteinase activity but also halved the NaTPI-insensitive fraction in third-instar larvae. Unable to degrade NaTPI, larvae apparently lacked the means to adapt to NaTPI in their diet. However, caterpillars recovered at least part of their gut proteinase activity when they were transferred from NaTPI-producing host plants to NaTPI-free host plants. In addition extracts of basal leaves inhibited more gut proteinase activity than did extracts of middle stem leaves with the same protein content. Conclusions/ significance Although larvae can minimize the effects of high NaTPI levels by feeding on leaves with high protein and low NaTPI activity, the host plant's endogenous NaTPIs remain an effective defense against M. sexta, inhibiting gut proteinase and affecting larval performance.